Identifying Maternal Depression in Pediatric Primary Care: Changes Over a Decade. Issue 2 (February 2016) - Kerker, Bonnie D.; Storfer-Isser, Amy; Stein, Ruth E. K.; Garner, Andrew; Szilagyi, Moira; O'Connor, Karen G.; Hoagwood, Kimberly E.; Horwitz, Sarah McCue
ABSTRACT: Objective: Maternal depression affects 10% to 40% of mothers with young children and has negative consequences for children's health and development. The American Academy of Pediatrics (AAP) recommends that pediatricians identify women with maternal depression. The authors examined trends in inquiring about (asking informal questions) or screening for (using a standardized instrument) maternal depression by pediatricians in 2004 and 2013 and identified correlates of usually inquiring/screening to identify maternal depression. Methods: Data were ascertained from 778 nontrainee pediatricians exclusively practicing general pediatrics who completed the 2004 (n = 457) and 2013 (n = 321) AAP Periodic Surveys. Pediatricians answered questions about physician and practice characteristics, training, attitudes, and inquiring/screening to identify maternal depression. Sample weights were used to reduce nonresponse bias. Weighted descriptive and logistic regression analyses were conducted. Results: The prevalence of usually inquiring/screening to identify maternal depression increased from 33% to 44% ( p < .01). In both years, pediatricians who usually inquired about child/adolescent depression had increased odds of usually inquiring/screening to identify maternal depression. Patient race/ethnicity and training in adult Diagnostic and Statistical Manual of Mental Disorders (DSM) diagnostic criteria for depression were associated with inquiring/screening in 2004, and believing that family screening is within the scope of the pediatrician was associated with inquiring/screening in 2013. Conclusion: Although inquiring/screening about maternal depression has increased since 2004, less than half of pediatricians usually screen or inquire about maternal depression, representing a missed opportunity to identify depression and manage or refer women for treatment. Further training on the importance of mental and family health to children's health may increase identification of maternal depression in pediatric primary care.